The Effect of Fibers Insertion on Fracture Resistance of Maxillary Premolar Teeth with MOD Cavity Restored with Composite (In Vitro Study) (Mustansiria Dental Journal, 2025)
Aim of the study: The purpose of this in vitro investigation was to compare the impact of different fibers on the fracture resistance of maxillary first premolar teeth with MOD cavities. Materials and methods: Sixty sound, non-carious human maxillary first premolars were selected for this study and randomly divided into four groups (n = 15). Groups A, B, and C consisted of intact teeth utilized as the control group, teeth restored with ribbond, and teeth restored with composite (Palfique LX5, Tokuyama, Japan) respectively. Group D included dental restorations using SFRC Ever X Posterior (GC, Japan). The occlusal surface of each tooth was imprinted using flowable composite material (stamp technique), and all teeth were mounted in a 2cm² square block of self-curing acrylic resin. A large class II MOD cavity preparation was performed for all groups except for Group A. The dimensions of the cavities were standardized as follows: the occlusal depth was 3 mm, the occlusal width buccolingually was 2/3 of the intercuspal distance, and the MO and DO boxes were prepared with a height of 1.5 mm at their axial walls. The teeth were tested in a universal testing apparatus with a 0.5 mm/min compressive load rate till fractures take until fractures occurred. The analysis of variance (ANOVA) and Tukey’s (HSD) tests were used to determine the statistical significance of the variation in fracture resistance among the groups under investigation, using a significance level of 0.05.Results: The results revealed that the groups restored with fibers (Group B and Group D) exhibited greater fracture resistance than group restored with composite only (Group C).Conclusions: In the context of the present investigation, teeth restored with Ribbond insertion demonstrated a significant increase in fracture resistance compared to the other tested groups, followed by teeth restored with Ever X posterior. In contrast, teeth restored with Tokuyama Palfique LX5 composite without fibers exhibited the least fracture resistance.